Improving demand responsive transit services: Insights from the London field test - Seyedmostafa Zahedi; Haris N. Koutsopoulos; Zhenliang Ma (Journal of Public Transportation)
The paper discusses the key insights gained from “GoSutton”, a Demand Responsive Transit (DRT) trial in the borough of Sutton in the suburbs of London during 2019–2020. The DRT service expands mobility options for the residents of the service area through the provision of on-demand, curb-to-curb rides. The main goals of the paper are to: 1) evaluate the performance of the DRT service and provide insight into its operation, 2) analyze the behavior of customers to better understand their purchase decisions and recommend strategies to increase ridership and usage, 3) develop a Level of Service (LOS) model to inform future trials on the interactions between supply, demand, and LOS, as well as identify key factors that impact performance, and 4) evaluate the opportunities to benefit from economies of scale through integrating appropriate paratransit requests and DRT services. The results show potential directions for improvement that can inform future deployments (for example, providing discounts for referrals, new users, providing bundles, and passes). Consolidation of select paratransit and DRT trips can save an average of 8 % on fleet size and 13 % on vehicle-kilometers traveled.